Navigating uncertainty: direct air capture and just transition perspectives in Gulf Coast communities - Celina Scott-Buechler; Katherine H Wang (Environmental Research Letters)
Direct air capture (DAC) projects are emerging in the Gulf Coast region of the United States, driven by recent private sector interest and federal funding. However, the role of these projects in facilitating a just transition for fossil fuel-dependent communities remains debated and uncertain. This study combines focus groups across three Gulf Coast sites with state-wide surveys in Texas and Louisiana to lend insights on community perspectives on DAC. Focus groups offer rich, qualitative insights into local concerns and aspirations, while the surveys provide broader quantitative data on regional attitudes. We find that DAC may be difficult to extract from the entrenched power of the fossil fuel industry and presents a need for careful planning to avoid social and economic upheaval in the wake of industrial transition. Community perceptions emphasize a dual nature of the fossil fuel industry: providing economic stability while also contributing to environmental and health injustices. While DAC emerges as a potential solution, requiring shared skillsets with the fossil fuel industry, community members express reservations about industry risks and historical lack of community engagement. Our findings underscore the importance of community involvement in decision-making (including when not to build), cooperative ownership models, and transparent processes. Both qualitative and quantitative results illustrate that community support for DAC is conditional on broader socio-economic benefits and inclusive governance, highlighting the need to consider these factors alongside technological features when planning DAC deployment in the region.